Women School Leaders: Entrepreneurs in Low Fee Private Schools in Three West African Nations - Cordeiro, Paula A.; Brion, Corinne (Frontiers in Education, 2018)
This study explores the opportunities and challenges of women who own low-fee private schools in three West African nations. With the implementation of the Millennium Development Goals (MDGs) in 2000 and the Sustainable Development Goals in 2016, it has become obvious to policymakers that school leadership needs to be a policy priority around the world. Increased school autonomy and a greater focus on schooling and school results have made it essential to understand and support the role of school leaders. Few countries however have strong and systematic initiatives to professionalize school leadership and to nurture and support current school leaders. This becomes even more complex for governments given the rise of private schooling in low and middle-income countries worldwide; thus, it is crucial for governments to understand the importance of leadership at the school level and how to nurture and professionalize it. In this study, the authors examine the roles of women school leaders in Burkina Faso, Ghana and Liberia within the context of MDG 3: promote gender equality and empower women, and explore the implications of the SDGs. Because of the many challenges in the public sector in education in low and middle-income countries, the private sector has responded by creating thousands of small businesses. Since a large and growing number of women are leading these private schools, this study presents the findings on the nature of the leadership of these women entrepreneurs. Fourteen school proprietors participated in face-to face interviews about their reasons for founding a school as well as the supports and challenges they face. Findings discuss the limited professional learning opportunities for school leaders in these nations. The study describes the school leaders’ desires to help build their nations, and the unique cultural and contextual factors in each country.